2015
DOI: 10.2514/1.c033099
|View full text |Cite
|
Sign up to set email alerts
|

Linear Reduced-Order Model for Unsteady Aerodynamics of an L-Shaped Gurney Flap

Abstract: Analysis of ballistic capture orbits in Sun–planet systems is conducted in this paper. This mechanism utilizes purely gravitational forces, and may occur in non-Keplerian regimes. Ballistic capture orbits are generated by proper manipulation of sets of initial conditions that satisfy a simple definition of stability. Six Sun–planet systems are considered, including the inner planets, Jupiter, and Saturn. The role of planets orbital eccentricity, their true anomaly, and mass ratios is investigated. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…This effect, which is consistent with the results of Refs. [18,19], may lead to possible drag increases compared to the baseline blade. Nevertheless, it will be hereinafter shown that no significant drag rises are encountered for both the actuated configurations.…”
Section: Results At Constant Angle Of Attackmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect, which is consistent with the results of Refs. [18,19], may lead to possible drag increases compared to the baseline blade. Nevertheless, it will be hereinafter shown that no significant drag rises are encountered for both the actuated configurations.…”
Section: Results At Constant Angle Of Attackmentioning
confidence: 99%
“…It is worth remarking that these results are in qualitative agreement with the assessments of Refs. [16][17][18][19][20], where the same effects were obtained with a mechanical L-tab deflected downward or upward, installed on a helicopter blade section. Additionally, the computed flow fields are qualitatively consistent with the Particle Image Velocimetry measurements of Feng et al [21] on a low-speed fixed wing section with PS plasma actuation opposite to the freestream direction.…”
Section: Results At Constant Angle Of Attackmentioning
confidence: 99%
See 3 more Smart Citations